Design and development of an automated mechanical valve for variable rate knapsack sprayer - Shamsi, Siti Mariam (2017)
Rice is a major crop in Malaysia that provides source of nutrition to the national population. Although rice farmers generally recognize the importance of fertilizer for supplying crops with essential nutrients needed for sustaining high yield, they often do not apply fertilizer at the right time and in the right amount to get a high return on their investment. The problem can be solved through precision farming; whereas sensors, navigation systems and machinery are integrated into a system called Variable Rate Applicator (VRA). So, the spraying will be done according to the needed soil and can practices the precision farming concept by the smallholder farmers. The design concept of VRA knapsack sprayer takes an idea from the shower diverter, which it can control from which outlet the liquid will flow through. Hence, the type fertilizer of fertilizer that can be applied by using the VRA knapsack sprayer is liquid forms. The VRA knapsack sprayer will spray the fertilizer based on desired application. For example, when the applicants arrive at the certain area that doesn’t need to apply the fertilizer, the valve will remain close. However, the pump will still running and the fertilizer will continuously flow and accumulates the pressurize fertilizer. In order to prevent the handle switch from blowing out, another line as a back flow line was proposed. The back flow was used when the main valve is closed to flow the fertilizer back to the tank. The valve will be controlled by the stepper motor in order to open and close the valve based on the desired application. The controller was designed to make sure it can be used suitably for the all knapsack type because the mechanism of the controller stand-alone without the disturbance from the operation of the knapsack itself. The mechanism of the controller was tested to open and close at the designated zone which is for zone A and C was set up as 90° of opening of valve while for zone B and D was set up as 45° opening of valve. It shows the controller successfully open and close based on the desire application with the average error of fertilizer application rate 1.38% and 0.92% respectively. The VRA knapsack sprayer was also compared with the normal knapsack to determine its efficiency. It shows the reduction of fertilizer used up to 27.3 % compared using the normal knapsack and it can help farmers to practice the precision farming concepts and saving the usage of fertilizers. So, a VRA knapsack sprayer that is small enough to be handled by a farmer and come with some intelligence has successfully been developed.